0733 The Bern Sleep-wake Registry: Demographics And Clinical Characteristics Of The First 6, 831 Patients. (27th April 2018) - Calle, M G; Dietmann, A; Bargiotas, P; Kallweit, U; Schmidt, M; Ott, S; Gugger, M; Mathis, J; Bassetti, C L
Abstract: Introduction: Most sleep registries reported in the literature include specific diagnostic groups. The largest registry across all sleep disorders was reported in 1982 and included nearly 5, 000 patient records from 11 U.S. sleep disorders centers. The aim of this study is 1) to report the demographics and clinical characteristics of the first 6, 831 patients included in our tertiary/academic Bern Sleep-Wake Registry and 2) to compare the results with the U.S. registry. Methods: Data from patients assessed between 2001 and 2015 at the sleep-wake center of the Neurology Department of the University Hospital Bern were transferred into an application designed to support data capture and management for research studies. Variables were analyzed descriptively. A validator was appointed to define research diagnoses derived from best-estimate procedures based on the International Classification of Sleep Disorders (ICSD-3) using medical history, hospital records, sleep-wake questionnaires (e.g. Bernese sleep-wake questionnaire which includes >100 items) and sleep-wake tests. Results: A total number of 6, 831 patients were included. Mean age was 49 ± 28 years and the male/female ratio was 2.33. Data from 6591 polysomnographies, 2852 vigilance tests (multiple sleep latency tests, maintenance of wakefulness tests), 2108 actigraphies and so far a subset of 1238 "Bernese sleep-wake questionnaires" were included. The most common diagnoses were sleep-related breathing disorders (63.8%, n=4355), insomnia (17.3%, n=1188), disorders of central hypersomnolence (13%, n=890 including 135 with narcolepsy and 382 with insufficient sleep syndrome), restless legs syndrome (6.5%, n= 443), parasomnias (5.3%, n=363) and circadian rhythm sleep disorders (1.1%, n=79). In comparison to the U.S. Registry, our Registry showed higher prevalence of restless legs syndrome and sleep-related breathing disorders and lower prevalence of narcolepsy, idiopathic hypersomnia, insomnia, circadian disorders and parasomnias. Conclusion: The Bern Sleep-Wake Registry is a large database covering the entire SWD spectrum, providing a new research tool for clinical sleep research, development of predictive models and validation of (new) diagnostic criteria or questionnaires. Support (If Any): N/A.